Can we plan services for children in foster care? Or do we just have to cope with what comes through the door? - Roger Bullock (Social Work & Society, 2017)
To what extent is it possible to plan ahead for children coming into care? How can we ensure that there are enough foster homes available for new entrants and that the range of facilities is sufficiently wide to meet all of their different needs? There are several possible approaches. We can wait and see what comes through the door and try to respond as best we can. Or, we can construct a range of services and try to fit the children into them. These strategies might be enough to contain the problem but will almost certainly lead to frustration, dissatisfaction and instability. So what else can be done? The Dartington Social Research Unit in England has developed a methodology to achieve a better match between the foster care that is provided and the needs of the children. It is called Matching Needs and Services (MNS).